Dietary flavanol intervention lowers the levels of endothelial microparticles in coronary artery disease patients. Issue 7 (14th April 2014) - Horn, Patrick; Amabile, Nicolas; Angeli, Franca S.; Sansone, Roberto; Stegemann, Berthold; Kelm, Malte; Springer, Matthew L.; Yeghiazarians, Yerem; Schroeter, Hagen; Heiss, Christian
<x content-type="archive" xml:space="preserve">Abstract</x> Current evidence suggests that regenerative v. degenerative endothelial responses can be integrated in a clinical endothelial phenotype, reflecting the net result between damage from risk factors and endogenous repair capacity. We have previously shown that a cocoa flavanol (CF) intervention can improve endothelial function and increase the regenerative capacity of the endothelium by mobilising circulating angiogenic cells in patients with coronary artery disease (CAD). The aim of the present study was to investigate whether CF can lower the levels of circulating endothelial microparticles (EMP), markers of endothelial integrity, along with improvements in endothelial function. The levels of EMP in the frozen plasma samples of CAD patients were measured along with endothelial function (flow-mediated vasodilation, FMD); n 16, FMD data published previously), and these data were compared with those of young (n 12) and age-matched (n 12) healthy control subjects. The CAD patients exhibited significantly increased levels of EMP along with impaired FMD when compared with the healthy control subjects. The levels of CD144+ and CD31+/41− EMP were inversely correlated with FMD (r − 0·67, P= 0·01 and r − 0·59, P= 0·01, respectively). In these CAD patients, the levels of EMP were measured after they had consumed a drink containing 375 mg of CF (high-CF intervention, HiFI) or 9 mg of CF (macro- and micronutrient-matched low-CF control, LoFl) twice daily over a 30-d period in a randomised, double-blind, cross-over study. After 1 month of HiFI, the levels of CD31+/41− and CD144+ EMP decreased ( − 25 and − 23 %, respectively), but not after LoFl. Our data show that flavanols lower the levels of EMP along with higher endothelial function, lending evidence to the novel concept that flavanols may improve endothelial integrity.